E com nossas devotas assistências e demonstrações se edifiquem os mais cristãos: educação moral e discurso pedagógico nas associações religiosas leigas - Minas Gerais, séculos XVIII e XIX - Paola Andrezza Bessa Cunha (2007)
This research has as objective analyses the speech in the Compromiseís Books of the Layman Religious Associations in Minas Gerais in the 18th and 19th centuries and its pedagogic dimensions as mediator of a civilized and moral speech. It was imperative the inhabitantís social control, which has a no- regulated life and worried the State, because that situation may turn in smuggling, rebellions and seditions. As in the Captaincy has not been the presence of scholar institutions, the instructions has happened in the most different spaces of soiability, most of al transmitted through good examples, that came from family, qualified people or acquaintanceís groups. The relation teaching-apprenticeship was in the little daily costumes, with the focus in the increasing of manís virtuoness, which takes to the social control and civility, understood as the peopleís treat. The analysis of the Portuguese civilized productions represented in the catechismís books, courtesyís handbooks and s of Portugueseís erudite indicate the attitude thatís makes a civilizationís project. The pedagogic speech in the Compromiseís Books corroborate that uniqueness of State and Society, revealing the predominate thought, that many times superpose other from devotionís nature in the deelopment of the good vassal and the good Christian, both full of virtue. The objective was evidence that the moral and educational speech of the 18th and 19th centuries intent to give the population the gestures and actionís control, civilizing and creating the best environment to Stateís control.